The Effect of Distraction Technique on Pain Intensity among Patients Undergoing Circumcision Anesthetic in Medan - Syamsul Idris; Ikhsanuddin Ahmad Harahap; Ridha Dharmajaya (Alta Dharma Publisher, 2020)
Circumcision actions often cause pain complaints when the anesthetic injection and post-circumcision are given to patients. Distraction aims to reduce pain response. Distraction by seeing and holding a needle is referred to as audiovisual distraction, which is a combination of hearing distraction (audio) and visual distraction to distract the patient's attention from the pain. This study aims to determine the effect of distraction technique on pain intensity among patients undergoing circumcision anesthetic. This study was a quasi-experimental design by using Two groups, pre-test, and post-test with the non-equivalent control group. The research sample consisted of 98 respondents who were divided into two groups taken by purposive sampling technique. The instrument used was the Wong-Baker Faces Pain Scale (WBFPS). Data analysis used was Bivariate Analysis by using Mann Whitney U Test. The result showed that the application of distraction technique to see and to hold a needle in the intervention group was influential in reducing the intensity of injection pain/anesthetic injections on circumcision clients compared to the control group (z = -8,881; p = 0,000). Based on the result of the study, it can be concluded that the application of a distraction technique to see and to hold needle affects to reduce the intensity of injection pain/anesthetic injections on circumcision clients. It is expected that the distraction technique of viewing and holding needle becomes an independent nursing intervention for an invasive procedure such as undergoing circumcision anesthetic